Geologically Recent Areas as One Key Target for Identifying Active Volcanism on Venus. Issue 22 (23rd November 2022) - D'Incecco, P.; Filiberto, J.; López, I.; Eggers, G. L.; Di Achille, G.; Komatsu, G.; Gorinov, D. A.; Monaco, C.; Aveni, S.; Mari, N.; Blackett, M.; Mastrogiuseppe, M.; et al.
Abstract: The recently selected NASA VERITAS and DAVINCI missions, the ESA EnVision, the Roscosmos Venera‐D will open a new era in the exploration of Venus. One of the key targets of the future orbiting and in situ investigations of Venus is the identification of volcanically active areas on the planet. The study of the areas characterized by recent or ongoing volcano‐tectonic activity can inform us on how volcanism and tectonism are currently evolving on Venus. Following this key target, Brossier et al. (2022, https://doi.org/10.1029/2022GL099765 ) extend the successful approach and methodology used by previous works to Ganis Chasma in Atla Regio. Here we comment on the main results published in Brossier et al. (2022, https://doi.org/10.1029/2022GL099765 ) and discuss the important implications of their work for the future orbiting and in situ investigation of Venus. Their results add further lines of evidence indicating possibly recent volcanism on Venus. Key Points: The manuscript by Brossier et al. (2022, https://doi.org/10.1029/2022GL099765 ) extends the successful approach and methodology used by previous work We comment here on the main results by Brossier et al. (2022, https://doi.org/10.1029/2022GL099765 ) and discuss the important implications for the future investigations of Venus Their results add further lines of evidence indicating possibly recent volcanism on Venus